A novel arthritis model induced by wind, damp, cold and heat in female rats. (October 2020) - Ge, Chuang; Hao, Jingchao; Wu, Xiaodong; Li, Chencheng; Zhi, Rui; Yu, Pengcheng; Wang, Xinmin; Hu, Jialiang; Xu, Hanmei
Animal models are in constant development to benefit scientific research. Rheumatoid arthritis (RA) is considered a very complex disease due to its complicated pathogenesis, and patients with rheumatic disease around the world are still unable to obtain effective, simple and curable treatment. In order to obtain a clear insight into the pathogenesis of RA, a rat model was established based on the concept of Bi syndrome in Traditional Chinese Medicine by simulating the conditions of RA as much as possible via the change in the physical conditions wind, damp, cold and heat (WDCH). For the first time, a new WDCH-induced RA model in female rats was successfully established and evaluated by body-weight change, paw swelling, blood cells analysis, spleen and thymus coefficients, autoantibodies and serum cytokine changes and histopathology. This model is characterised by its objectivity, no exogenous induction, short modelling time, extremely elevated expression level of autoantibodies and obvious histopathological change. The establishment of such a new model may provide more benefits in the research of the pathogenesis of RA.